2018
DOI: 10.1111/jgs.15337
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Home Visits for Individuals with Advanced Parkinson's Disease and Related Disorders

Abstract: Parkinson's disease (PD) is a complex, multisymptom, neurodegenerative disease affecting primarily older adults. With progression, many individuals become homebound and removed from coordinated, expert care, resulting in excess morbidity, mortality, and healthcare expenditures in acute care settings and institutions. Home visit care models have achieved the triple aim of improving individual and population health while reducing costs in many frail, community-dwelling geriatric cohorts. This study details a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 48 publications
(48 reference statements)
0
50
0
2
Order By: Relevance
“…We included 48 records in the qualitative review, from which 37 studies met the inclusion and exclusion criteria. The study characteristics of 8 randomized, controlled trials (RCTs) included in the quantitative meta‐analysis and 19 other experimental studies included in the systematic review are presented in Table . The remaining 10 articles included in our systematic review were nonexperimental (ie, review articles or descriptions of care models) and are detailed separately in Supplementary Table 1 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 48 records in the qualitative review, from which 37 studies met the inclusion and exclusion criteria. The study characteristics of 8 randomized, controlled trials (RCTs) included in the quantitative meta‐analysis and 19 other experimental studies included in the systematic review are presented in Table . The remaining 10 articles included in our systematic review were nonexperimental (ie, review articles or descriptions of care models) and are detailed separately in Supplementary Table 1 …”
Section: Resultsmentioning
confidence: 99%
“…2 for geographical map), although large parts of the world remained underrepresented. Table presents the characteristics and results of all studies, including the RCTs included in the meta‐analysis, as well as other studies included in the systematic review (nonrandomized, controlled trials, pretest/posttest designs, observational cohort studies, and retrospective chart reviews) . In the online supplementary materials, Supplementary Table 1 presents articles with detailed descriptions of proposed care models and other related reviews of care models specific to integrated care in PD .…”
Section: Resultsmentioning
confidence: 99%
“…Recognition and management of complexity is likely to improve quality of life and prognosis for patients [ 55 ]. A more biopsychosocial model of care [ 56 ] that comprises regular, comprehensive patient assessment by an integrated team; case management; personalised care plans, prioritising patients’ goals and preferences; self-management support for patients [ 57 ] is advocated, feasible and successful [ 58 ]. Future research studies should seek to enrol patients who are representative of the population living with PD, multimorbidity and frailty to make findings generalisable to this prevalent, yet under-represented group.…”
Section: Discussionmentioning
confidence: 99%
“…26 Dr. Jori Fleisher and colleagues have demonstrated the feasibility and value of providing such care from a Parkinson' specialist, nurse, and social worker. 27 House calls are the gold standard of patient-centered care but are time-and resource intense. Indeed, a recent study in Germany found that many patients with Parkinson's disease were ineligible to receive a house call by a Parkinson's nurse specialist simply because travel distances were too long.…”
Section: Clinic-centered Carementioning
confidence: 99%